Reticuloendothelial function in renal allograft recipients. - Drivas, G (1975)
The phagocytic capacity of the reticuloendothelial system (R.E.S.) was assessed in patients with chronic renal failure and in renal transplant recipients. R.E.S. phagocytosis was increased in the former group. Soon after transplantation R.E.S. phagocytosis was moderately reduced (through levels were comparable with those of normal controls) but was particularly reduced after high-dose corticosteroid treatment for rejection. In long-term allograft recipients R.E.S. phagocytosis was also depressed though steroid maintenance doses were small.